Groundwater potential zonation using VES and GIS techniques: A case study of Weserbi Guto catchment in Sululta, Oromia, Ethiopia - Desalegn Dhinsa; Fekadu Tamiru; Birhanu Tadesa (Heliyon, 2022)
Groundwater is an appreciated and vital natural resource in the world, and it is of the utmost essential for the growth and development of a country. Nevertheless, assessing the groundwater potential and its recharge region is still ambiguous due to the nature of groundwater. In this study, the groundwater potential of the Weserbi Guto Laga Qawe Catchment Sululta area was assessed using VES and GIS methods. For the model, thematic layers were generated from the geophysical investigation, existing maps, and field survey results and were integrated into the GIS environment to delineate the groundwater potential zones. Factors such as lineament density, drainage density, elevation or topography, slope gradient, aquifer resistivity, and lithology were derived, reclassified, and scaled to common ranges and assigned with appropriate weights. The groundwater potential zonation model of the site was produced by the multicriteria evaluation method. Accordingly, the geometrical interval method was utilized to classify the index into three zones (high, moderate, and low) to produce the map. The model result revealed that a large part of the study area fell into the high zone with 50.14 % (3669.99ha). whereas 35.85% (262.72ha) and 14.01% (1024.95ha) show moderate and low groundwater potential, respectively. The resulting map was validated using eleven existing water level data points and the result was found to be in good agreement with the model.